PERANAN MOTIVASI BERPRESTASI DAN PERHATIAN DALAM BELAJAR (STUDI PADA MAHASISWA TAHUN PERTAMA JURUSAN KESEHATAN LINGKUNGAN POLITEKNIK KESEHATAN MALUKU) - Nurlaila Marasabessy; Lucky Herawati; Hairudin Rasako; Jumarni Ely (Poltekkes Kemenkes Maluku, 2018)
The quality and quantity of learning is influenced by several things, including student motivation andattention. This study aims to identify the role of motivation and attention in learning, especially in thefirst year students of the Health Polytechnic of Moluccas on Environmental Health Department. Thisstudy uses quantitative design, involving 80 first-year students in 2011/2012. The Archer InstrumentModification for the Health Professional Motivation Survey1 is used to measure motivation, whilemeasuring attention using Attention Deficit / Hyperactivity Disorder (ADHD) 2. The results showedthat the achievement motivation of first-year students was oriented towards meeting academicrequirements, while the results of attention measurement found that most students had difficulty givingattention (ADHD) in the medium category. Keywords: motivation, attention, learning, student